The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ma15248973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Argon on the Properties of Copper Nitride Fabricated by Magnetron Sputtering for the Next Generation of Solar Absorbers

Abstract: Copper nitride, a metastable semiconductor material with high stability at room temperature, is attracting considerable attention as a potential next-generation earth-abundant thin-film solar absorber. Moreover, its non-toxicity makes it an interesting eco-friendly material. In this work, copper nitride films were fabricated using reactive radio frequency (RF) magnetron sputtering at room temperature, 50 W of RF power, and partial nitrogen pressures of 0.8 and 1.0 on glass and silicon substrates. The role of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…It should be emphasized that the values of the index of refraction reported in our present ellipsometric study are clearly much higher than those measured for Cu 3 N with the prism coupling technique [24]. We considered that the values of the refractive index found with the latter technique, surprisingly, around 1.5 at four wavelengths in the NIR region, are notably underestimated, taking into account that the values of the refractive index determined in our study are very consistent with those previously reported in the literature [25], calculated making use of the popular Swanepoel transmission-envelope method.…”
Section: Uv-mir Ellipsometric Analysiscontrasting
confidence: 82%
“…It should be emphasized that the values of the index of refraction reported in our present ellipsometric study are clearly much higher than those measured for Cu 3 N with the prism coupling technique [24]. We considered that the values of the refractive index found with the latter technique, surprisingly, around 1.5 at four wavelengths in the NIR region, are notably underestimated, taking into account that the values of the refractive index determined in our study are very consistent with those previously reported in the literature [25], calculated making use of the popular Swanepoel transmission-envelope method.…”
Section: Uv-mir Ellipsometric Analysiscontrasting
confidence: 82%
“…Du et al [ 40 ] also observed a sudden drop in the measured electrical resistivity of the (111)-oriented Cu 3 N material, due to an additional conductance mechanism, causing the percolation effect to come into play, which was not beneficial when using such oriented material as a solar absorber. Finally, it should be pointed out that the number of diffraction peaks that appeared in the patterns of the samples fabricated in the N 2 pure environment (see Figure 3 ) were less than those obtained in our previous work for the samples fabricated in a mixture of Ar and N 2 [ 33 ]. This fact could positively contribute to minimizing trapping centers due to the reduction of grain-orientation effects, being indicative of a better crystal quality.…”
Section: Resultsmentioning
confidence: 54%
“…This work presents the fabrication of a Cu 3 N binary compound by reactive RF magnetron sputtering at RT in a pure N 2 environment by modifying the RF power and the total working pressure. In our previous works, we observed that the use of an argon (Ar)-free environment during the sputtering process led to films with better structural quality, the (100) plane being the preferential orientation, and smoother surfaces when Ar was used during the sputtering process [ 33 ]. Considering that the design of desired functional material properties by controlling deposition parameters is a key technological topic, in this work, we establish the crystal nature, morphology, electrical and optical properties of the deposited Cu 3 N films as functions of the preparation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we determined that the fact of not using Ar during the sputtering process led to the obtaining of Cu 3 N films with improved structural quality, with the (100) plane as preferential orientation and smoother surfaces than when using Ar–N 2 gas mixture as process gas. [22] For this reason, in this work, the N atmosphere is preferred. It is expected to determine the optimised RF values and the N gas pressure range to obtain Cu 3 N films with appropriated morphologies, structures and band gap energies, suitable for the chosen application of emerging light absorber to replace silicon.…”
Section: Introductionmentioning
confidence: 99%